2021
DOI: 10.1038/s41396-020-00880-z
|View full text |Cite
|
Sign up to set email alerts
|

Mesopelagic microbial carbon production correlates with diversity across different marine particle fractions

Abstract: The vertical flux of marine snow particles significantly reduces atmospheric carbon dioxide concentration. In the mesopelagic zone, a large proportion of the organic carbon carried by sinking particles dissipates thereby escaping long term sequestration. Particle associated prokaryotes are largely responsible for such organic carbon loss. However, links between this important ecosystem flux and ecological processes such as community development of prokaryotes on different particle fractions (sinking vs. non-si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(71 citation statements)
references
References 84 publications
7
64
0
Order By: Relevance
“…Changes in prokaryotic communities were distinguished most notably by depth (ANOSIM by depth: R = 0.82, p = 0.001), with some seasonal separation evident (ANOSIM season by depth: R = 0.62, p = 0.001) (Adonis season by depth: F = 5.8, p = 0.001), particularly for winter samples which were more clearly separated for both depths (Figure 2B). Many other studies have also observed community changes with depth across global oceans (Cram et al, 2015;Luna et al, 2016;Mestre et al, 2018;Richert et al, 2019;Baumas et al, 2021). This was consistent with an increase in community dissimilarity as communities transitioned from spring to winter in surface samples (KW surface: Chi-squared = 41.897, df = 3, p < 0.001) (Figure 2C).…”
Section: Surface Phytoplankton Blooms Drive Seasonality In the Deep Oceansupporting
confidence: 83%
See 1 more Smart Citation
“…Changes in prokaryotic communities were distinguished most notably by depth (ANOSIM by depth: R = 0.82, p = 0.001), with some seasonal separation evident (ANOSIM season by depth: R = 0.62, p = 0.001) (Adonis season by depth: F = 5.8, p = 0.001), particularly for winter samples which were more clearly separated for both depths (Figure 2B). Many other studies have also observed community changes with depth across global oceans (Cram et al, 2015;Luna et al, 2016;Mestre et al, 2018;Richert et al, 2019;Baumas et al, 2021). This was consistent with an increase in community dissimilarity as communities transitioned from spring to winter in surface samples (KW surface: Chi-squared = 41.897, df = 3, p < 0.001) (Figure 2C).…”
Section: Surface Phytoplankton Blooms Drive Seasonality In the Deep Oceansupporting
confidence: 83%
“…This event may have influenced seasonal patterns as highlighted in Chl-a and bacterial production levels which typically peak during summer/early autumn but were absent for 2016. Bacterioplankton production and abundance generally decrease with depth (Nagata et al, 2000) and production has recently been shown to be negatively correlated with species richness 2 weeks after a surface phytoplankton bloom (Baumas et al, 2021). Ruiz-González et al (2020) explored changes in bacterial abundance and production across different stations in relation to surface properties, and found linkages between prokaryotic production from bathypelagic layers and surface microplankton (20-200 µm) groups and surface dissolved organic matter quality.…”
Section: Surface Phytoplankton Blooms Drive Seasonality In the Deep Oceanmentioning
confidence: 99%
“…Previous studies examining particle-attached microorganisms, including those at Sta. ALOHA, have found elevated relative abundances of many of the same copiotrophic genera we describe in our particle-amended treatments (Fontanez et al 2015;Farnelid et al 2019;Baumas et al 2021). Intriguingly, although sinking particles were selectively enriched in these putative copiotrophs, in our study, the particulate C normalized rates of production from our particle-amended treatments were similar to controls.…”
Section: Microorganism Production and Community Compositionsupporting
confidence: 64%
“…Such findings are consistent with a study in the North Atlantic (conducted between 5°N and 35°N), where suspended particles were suggested to constitute an important source of C supporting mesopelagic bacterial metabolism (Baltar et al 2009). However, at higher latitudes in the North Atlantic (49°N), microorganism growth rates associated with rapidly sinking particles were found to exceed growth rates of microorganisms associated with slowly or nonsettling particles (Baumas et al 2021). We were unable to determine the extent to which small and large particles were colonized by microorganisms in our experiments because we did not measure abundances of microorganisms attached to sinking particles; however, when we normalized our rate measurements to measured particulate C concentrations (which would include the biomass contributions of particle‐associated microorganisms), production rate constants in the particle‐enriched treatments were similar to those in the unamended controls.…”
Section: Discussionmentioning
confidence: 99%
“…Using a marine snow catcher device, Baumas et al [15] recently studied the link between diversity and activity of prokaryotes associated with freshly collected gravitational sinking particles at the Porcupine Abyssal Plain site (PAP site) in the Eastern North Atlantic Ocean. To complement these observations, we hereby present a laboratory biodegradation experiment carried out during the same field sampling campaign (DY032 cruise).…”
Section: Introductionmentioning
confidence: 99%